Study of thermal and mechanical properties of a biocomposite based on natural rubber and 45S5 Bioglass® particles - Silva, M. J. [UNESP]; Soares, V. O.; Dias, G. C.; Santos, R. J. [UNESP]; Job, A. E. [UNESP]; Sanches, A. O. [UNESP]; Malmonge, J. A. [UNESP] (Springer Nature, 2018)
Biocomposites based on natural rubber (NR) reinforced with 45S5 Bioglass® (BG) particles were obtained by casting/evaporation method in which NR was dissolved in chloroform and mixed with BG particles. Structural, mechanical, and thermal tests were performed on the biocomposites to evaluate the influence of BG particles on the properties of the NR matrix. Thermogravimetric tests (TG/DTG) of the biocomposites showed decomposition profiles similar to that of NR, and the main peak of the DTG curve was well defined in the temperature range 300–450 °C, characteristic of the structural degradation of NR. The TG analysis also revealed that the thermal stability of the samples increases with the increasing quantity of BG in the biocomposite. DMA tests showed higher storage modulus (E′) values for samples with larger amounts of BG; however, above the Tg, the E′ value tended to zero due to the increased mobility of the polymer chains. By analyzing tan δ, the Tg values were calculated to be −46 and −50 °C for NR and the biocomposite samples, respectively. Mechanical testing demonstrated that the addition of BG to the biocomposite improved the mechanical properties of the samples. The samples became more rigid with the increasing quantity of BG, as demonstrated by decreasing deformation and the increasing elastic modulus (Y) and breaking strength of the samples. The BG particles positively affected the mechanical and thermal properties of the biocomposite, allowing its use in biomedical applications.
Keywords: Biocomposite; Bioglass®; Mechanical analysis; Natural rubber; Thermal analysis